The holiday [videorecording (Blu-Ray)] - Meyers, Nancy; Diaz, Cameron; Winslet, Kate; Law, Jude, 1972-; Black, Jack, 1969- (Sony Pictures Home Entertainment, 2007)
Iris and Amanda are both coming out of long term relationships and looking for a change. They meet online on a home exchange website and impulsively decide to switch homes for the Christmas holidays. Unexpectedly, and quite to their surprise, not only do they find a new home but a new love.